Whitehead’s Processual Conception of Nature. (Nóema, 2020)
The metaphysics of process, of which Process and Reality is the manifesto and the implementation, does not arise from nothing, but on the contrary emerges from a complex and prolonged meditation conducted by Whitehead since the first writings, of a logical and mathematical character, and then passes through an articulated reflection on the fundamental problems of the epistemology of natural sciences, conducted in the light of the conceptual revolution generated by the research of Einstein but also of many other scholars.In order to situate the fundamental notions developed by Whitehead in his so-called "speculative" period in its correct theoretical context, it is fundamental to outline the theoretical framework from which these notions emerge, to show that they do not represent, as someone has argued, a deviation, but on the contrary, a coherent development of the mathematical, logical and epistemological premises on which the English mathematician and philosopher has never ceased to investigate (even after the great works of the 1920s). In this way it is possible to appreciate both the philosophical content of apparently different writings and the genuine sense of terms that otherwise remain wrapped in an obscurity often denounced but more rarely understood. The speculative notions of actual entity, eternal object, process, concrescence and so on are understandable only when viewed in this key, at the same time genetic and genealogical.
Keywords: Whitehead; algebra of logic; space-time; relativity theory; process; event; object; relations